DESAIN SISTEM PENDATAAN KEHADIRAN KARYAWAN TERINTEGRASI FINGERPRINT DENGAN FUNGSI PENGATURAN SHIFT KERJA BERBASIS VISUAL - Ahmad Zainudin; Lutfil Hakim Arif Efendi (STEKOM PRESS, 2019)
Data collection on employee attendance at a company is a must, with the aim of monitoring discipline, calculating employee salaries, and other needs. Data collection on employee attendance at companies that are used today is very diverse, following the development of technology. The United Tronik Semarang office, which employs relatively many employees, currently uses a manual card attendance data collection system that attracts researchers to make the United Tronik Office the object of research. Fingerprint is one of the hardware used to support employee attendance data collection which is relatively simple and easy to reach, the accuracy and ease of operation make the fingerprint attendance system more and more in demand. One of the human error problems in the attendance data collection system is attendance recording errors, especially for employees with shift work hours. Arrangement of work shifts in programs built with Visual Basic 2010 can minimize attendance recording errors, because it can set the recording time for employees. To support the ease of data access and shift settings, the researcher uses a Client Server database system with SQL Server 2005 Software.